Poverty focussed rural good governance in Asian Commonwealth countries : Commonwealth Secretariat-CIRDAP Workshop on Sharing Successful Experiences on Poverty Focused Rural Good Governance in Asian Commonwealth Countries : 27-31 May, 2006, CIRDAP, Dhaka, Bangladesh - Commonwealth Secretariat-CIRDAP Workshop on "Sharing Successful Experiences on Poverty Focused Rural Good Governance in Asian Commonwealth Countries" (2006 : CIRDAP); Sudhakar Rao, B.; Center on Integrated Rural Development for Asia and the Pacific; Commonwealth Secretariat (Dhaka : Centre on Integrated Rural Development for Asia and the Pacific, 2008)
Papers presented at the workshop; with reference to South and Southeast Asian countries; workshop organized by Commonwealth Secretariat and Center on Integrated Rural Development for Asia and the Pacific.
Includes bibliographical references.
Keywords: Rural development -- Government policy -- South Asia -- Congresses; Rural development -- Government policy -- Southeast Asia -- Congresses; Local government -- South Asia -- Congresses